Pleuranthodium replaces the illegitimate Psychanthus (Zingiberaceae) - Smith, R. M. (Edinburgh Journal of Botany, 2010)
Twenty-two species of Alpinia previously placed under the illegitimate name Psychanthus (K. Schum.) Ridley arc transferred to Pleuranthodium (K. Schum.) R. M. Smith.